Freshwater Zooplankton diversity of Halali reservoir: A Review - Wasarat, Mohd; Chauhan, Rajendra (International Journal of Scientific Research in Biological Sciences, 2018)
Investigations on Zooplankton species were conducted monthly using standard methods in Halali reservoir between Mar. 2016 to Feb. 2017. The plankton fauna of the state of madhya pardesh, central India, especially in the Betwa basin, is still poorly known. Thus, this paper presents data from samples taken recently from different sites in Halali. A total of 23 species were recorded, including 13 new occurred rotifers, 07 of cladocerans and 03 of copepods for the state of Halali. The maximum richness was seen for the rotifers, of which the Genus Brachionus have to be highlighted, mainly at the Halali reservoir.